2013
DOI: 10.1007/s12094-013-1006-4
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab plus preoperative chemotherapy in operable HER2 negative breast cancer: biomarkers and pathologic response

Abstract: PurposeThe primary aim of this trial was to assess the rate of pathologic complete responses (pCR) of doxorubicin/cyclophosphamide (AC) followed by bevacizumab/docetaxel (BT), as neoadjuvant therapy for breast cancer (BC). Furthermore, the association between biomarkers and the pCR was explored.MethodsPatients with HER-negative operable stage II–III BC ≥2 cm were enrolled. Four cycles of AC (A 60 mg/m2 and C 600 mg/m2, every 3 weeks) followed by 4 cycles of BT (B 15 mg/kg and T 75 mg/m2, every 3 weeks), were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Although the observations are not statistically significant after correction of multiple testing, correlation of low NRP1 expression and BEV effect was consistent with the early observing in gastric and colorectal cancer, which made NRP1 one of the most promising markers identified thus far. Besides translational research in phase III clinic trials, AGTR1 overexpression has been found associated with greater treatment response of BEV in several phase II studies (62,63).…”
Section: Angiogenic Gene Expression In Situmentioning
confidence: 99%
“…Although the observations are not statistically significant after correction of multiple testing, correlation of low NRP1 expression and BEV effect was consistent with the early observing in gastric and colorectal cancer, which made NRP1 one of the most promising markers identified thus far. Besides translational research in phase III clinic trials, AGTR1 overexpression has been found associated with greater treatment response of BEV in several phase II studies (62,63).…”
Section: Angiogenic Gene Expression In Situmentioning
confidence: 99%
“…In another subset of 178 HER2-negative breast tumor patients, high AT1 expression was identified as a marker of resistance to anthracyclin-based neoadjuvant chemotherapy ( de Ronde et al, 2013 ). Recent studies further suggested that high AT1 level may be a predictive marker of bevacizumab response in breast tumors ( Sánchez-Rovira et al, 2013 ; Salvador et al, 2014 ). Of interest, bevacizumab-induced hypertension in breast cancer patients was also associated with better overall response to this anti-angiogenic therapy ( Gampenrieder et al, 2014 ).…”
Section: Angiotensin Receptors In Breast Cancermentioning
confidence: 99%
“…Primary outcome measures will be available in June 2016, and completion is expected in January 2019 21 . The angiotensin ii receptor type 1 has also recently been hypothesized to be a marker predictive of response to bevacizumab 34,35 . Hypertension has also been suggested to be a predictive marker of bevacizumab efficacy, and a retrospective analysis suggested a predictive value of hypertension as a marker of response to bevacizumab 36 .…”
Section: Patient Profilementioning
confidence: 99%